1990
DOI: 10.1063/1.345622
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity enhancement of poly-ether-ether-ketone by ion implantation

Abstract: Articles you may be interested inDielectric characteristics of poly(ether ketone ketone) for high temperature capacitive energy storage Appl. Phys. Lett. 95, 022902 (2009); Molecular dynamics and microstructure development during cold crystallization in poly(ether-ether-ketone) as revealed by real time dielectric and x-ray methods Relaxation behavior in model compounds of poly(aryl-ether-ketone-ketone) as revealed by dielectric spectroscopy Effects of the lowsurfaceenergy component on the viscosity of poly(eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In some instances the microhardness of the irradiated surface can be substantially increased (up to 50 to 70 times 122 ± 126 ). These effects were observed for various polymers, namely, polyimide, 28,123,126 polystyrene, 122,123 polyethylene, 92,127 129 and some other polymers irradiated with different (mostly light and not too heavy) ions with energies ranging from 100 keV to 1 MeV. The microhardness of carbonaceous products is first of all determined by the character of interconnectivity within the carbon cluster aggregates.…”
Section: Peculiarities Of the Morphology And Properties Of Ion-implan...mentioning
confidence: 99%
See 1 more Smart Citation
“…In some instances the microhardness of the irradiated surface can be substantially increased (up to 50 to 70 times 122 ± 126 ). These effects were observed for various polymers, namely, polyimide, 28,123,126 polystyrene, 122,123 polyethylene, 92,127 129 and some other polymers irradiated with different (mostly light and not too heavy) ions with energies ranging from 100 keV to 1 MeV. The microhardness of carbonaceous products is first of all determined by the character of interconnectivity within the carbon cluster aggregates.…”
Section: Peculiarities Of the Morphology And Properties Of Ion-implan...mentioning
confidence: 99%
“…Therefore the conductivity, which is proportional to the optical absorption of the carbonaceous phase, 131 only indirectly depends on the nature of implanted ions, being mainly determined by the energy loss during the stopping of ions. 1,17,21,129 Since the conducting phase in the ionimplanted layer is formed by discrete carbon clusters and their associates, the onset of conductivity in an irradiated polymer upon build up of implantation dose has a threshold character (see Fig. 3) and the transition from dielectric to conductor can be considered as percolation transition.…”
Section: Peculiarities Of the Morphology And Properties Of Ion-implan...mentioning
confidence: 99%
“…It is well reported in literature that ion implantation may reduce the crystallinity, induce cross-linking and produces carbonyl groups on the polymers [16][17][18][19], which results in polymer degradation. Most studies in the field have shown significant surface carbonization and splitting of chemical bonds on the side of the polymer chain in ion implanted polymers [20][21][22]. Polymer chain splitting was reported for polymers implanted with ions [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, optical, mechanical, electrical and chemical properties can be selectively modified using ion beam bombardment (Solfield et al 1993;Vacik et al 1997). Ion irradiation of polymer is followed by the processes of macromolecular distribution, cross-linking, free radicals formation, carbonization and oxidation (Bedell et al 1990;Hnatowicz et al 1994). Therefore, understanding of certain structural rearrangements of the polymer composites opens a way to design devices with required parameters.…”
Section: Introductionmentioning
confidence: 99%